Identification for Development Country Diagnostic : Uganda - World Bank (World Bank, Washington, DC, 2019)
In today’s digital age, robust, inclusive, and responsible civil registration and identification systems play an important role in providing citizens with a legal identity and generating vital and demographic statistics. Universal coverage of these systems improves the accessibility, integrity, effectiveness, and efficiency of public and private services. Experience in Estonia, India, Peru, South Africa, Thailand, and other countries has shown that an effective national identification system can accelerate progress in addressing key development and governance challenges, such as financial inclusion, universal healthcare coverage, and digitizing and integrating services in the public and private sectors. The ID4D diagnostic was undertaken between November 2017 and June 2018 at the request from the Ministry of Internal Affairs of the Government of Uganda under the umbrella of the World Bank’s Identification for Development (ID4D) initiative.This work was done with excellent collaboration from NIRA’s management and personnel. Its objective was to analyze the identification ecosystem in Uganda, highlight strengths and achievements, suggest areas of improvement, and build consensus around recommendations and next steps. This was done through in-person interviews with over40 government and private stakeholders, a field visit, and a literature review. Draft findings and recommendations were presented at a consultation workshop in August 2018, attended by over 50 experts representing 30 MDAs and private sector organizations. Feedback from the workshop is reflected in the report.